(untitled) (Al-Academy, 2021)
Reduction represents a form of artistic abstraction to express things with formal symbols that suggest the content of the idea, as the beauty of the design artwork cannot be unique in the form only, but in revealing its meaning as well. He resorts to shorthand to express the content of his idea related to design necessities and needs to achieve a specific function whose role is crystallized through the form that follows the function. The importance of the research was also represented in: Benefiting workers and scholars in the field of design with regard to shorthand and implicit in graphic design. The aim of the research: to identify the relationship between implicit meaning and reduced forms in graphic design. And the aesthetic of formal reduction. Then the indicators of the theoretical framework, then the research procedures, the research community and the research tool. The results and conclusions, and the most important results: The use of reduced drawings in the design structure of the implicit idea achieved a clear reduction of many ideas in the mind of the recipient. And concluded with recommendations, sources and references